Strain control in germanium nanowires: the use of a silicon nitride shell. Issue 4 (17th March 2014) - Dupré, Ludovic; Buttard, Denis; Gentile, Pascal; Benoit à la Guillaume, Quentin; Gorisse, Thérèse; Renevier, Hubert
Abstract The core–shell geometry is a strong tool for inducing and controlling strains in nano‐objects in order to tune their optoelectronic properties. We synthesized and characterized core–shell nanostructures by depositing a non‐epitaxial silicon nitride shell around germanium nanowires. Scanning electron microscopy as well as energy dispersive X‐ray spectroscopy confirms the structural integrity of the heterostructures, and grazing incidence X‐ray diffraction measurements reveal the presence of a radial tensile strain in the Ge nanowires. A control of this strain is then demonstrated up to 0.3% by adjusting the SiNx shell thickness versus Ge nanowire diameter. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)